Ontology-driven use of ChatGPT to build guidelines and select technology parameters for IoT lab development - Adam Doering; Łukasz Kryła; Maciej Kamiński; Łukasz Muszarski; Cezary Orłowski; Marek Ożarowski (Journal of Information and Telecommunication)
A new approach is presented concerning the development of IoT laboratories based on the proposals of ChatGPT supported by ontologies. In the first stage, ChatGPT was used to build guidelines for the development of the IoT laboratory. On this basis, in the second stage, a student project was prepared to build an Apache Kafka message broker. In the third stage, this project was the basis for building ontology of concepts for building queries for ChatGPT. Then, in the fourth stage, ChatGPT's ontology-based proposals were used to select the technological parameters of the developed laboratory. Conclusions suggest that ChatGPT in the construction of guidelines and the need to use ontology for the selection of technological parameters.